Suppose PQ has P(a,b) and midpoint M(c,d). What is an expression for PM? Use the expression for PM to find an expression for PQ.
PM= ________

Respuesta :

Answer:

[tex]PM = \sqrt{(a - c)^2 + (b-d)^2}[/tex]

Step-by-step explanation:

Relevant data provided as per the requirement of question is shown below:-

M(c,d)is a midpoint of PQ

PM = MQ

The expression for PM to find an expression for PQ is shown below:-

Where,

[tex]PM = \sqrt{(a - c)^2 + (b-d)^2}[/tex]

Which is equals to MQ

and

[tex]MQ = \sqrt{(a - c)^2 + (b - d)^2}[/tex]

For more clarification, the diagram has been presented below:-

I______I______I

P           M          Q

(a,b)     (c,d)

ACCESS MORE